Draft genome sequence of Enterobacter cloacae HBY, a ST128 clinical strain co-producing KPC-2 and NDM-1 carbapenemases. (March 2018) - Li, Xi; Zhu, Yongze; Shen, Mengyuan; Du, Jing; Zhang, Lei; Wang, Dairong
Abstract: Objectives: Enterobacter cloacae is one of the major pathogens responsible for a variety of human infections. Here we report the draft genome sequence of multidrug-resistant E. cloacae strain HBY isolated from a female patient in China. Methods: Whole genomic DNA of E. cloacae strain HBY was extracted and was sequenced using an Illumina HiSeq™ 2000 platform. The generated sequence reads were assembled using CLC Genomics Workbench. The draft genome was annotated using Rapid Annotations using Subsystems Technology (RAST), and the presence of antimicrobial resistance genes was identified. Results: The 5 799 439-bp genome contains various antimicrobial resistance genes conferring resistance to aminoglycosides, β-lactams, fosfomycin, macrolides, sulphonamides and fluoroquinolones. Notably, the strain was identified to carry two main carbapenemase genes ( bla KPC-2 and bla NDM-1 ). Conclusions: The genome sequence reported in this study will provide valuable information to understand antibiotic resistance mechanisms in this strain. It is important to monitor the spread strains of Enterobacter sp. encoding both of these carbapenemase genes.